The use of a new calcium mesoporous silica nanoparticle versus calcium and/or fluoride products in reducing the progression of dental erosion - Fernanda Michel Tavares CANTO; Adílis Kalina ALEXANDRIA; Isabela B. dos Santos JUSTINO; Gustavo Miranda ROCHA; Lúcio Mendes CABRAL; Raphael da Silva FERREIRA; Matheus Melo PITHON; Lucianne Cople MAIA
Abstract Objective There is increasingly common the consumption more times a day of foods and acidic drinks in the diet of the population. The present study aimed to evaluate and compare the effects of a calcium mesoporous silica nanoparticle single application of other calcium and/or fluoride products in reducing the progression of dental erosion. Methodology Half of the eroded area was covered of 60 blocks of enamel, after which the block was submitted to the following treatments: (Ca2+-MSN), casein phosphopeptide-amorphous calcium phosphate (CPP-ACP); CPP-ACP/F-(900 ppm F−); titanium tetrafluoride (TiF4 1%) (positive control); sodium fluoride (NaF 1.36%) (positive control); and Milli-Q® water (negative control) before being submitted to a second erosive challenge. A surface analysis was performed via a three-dimensional (3D) noncontact optical profilometry to assess the volumetric roughness (Sa) and tooth structure loss (TSL) and and through scanning electron microscopy (MEV). An analysis of variance (ANOVA) and Tukey's test were performed. Results Regarding Sa, all experimental groups exhibited less roughness than the control (p<0.05). The TSL analysis revealed that the Ca2+-MSN and NaF groups were similar (p>0.05) and more effective in minimizing tooth loss compared with the other groups (p<0.05). Conclusions The Ca2+-MSN and NaF treatments were superior compared with the others and the negative control.